2011
DOI: 10.2105/ajph.2009.190009
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Disparities in Childhood Sexual Abuse, Parental Physical Abuse, and Peer Victimization Among Sexual Minority and Sexual Nonminority Individuals

Abstract: Objectives We compared the likelihood of childhood (i.e., <18 years) sexual abuse, parental physical abuse, and peer victimization based on sexual orientation. Methods We conducted a meta-analysis of adolescent school-based studies that compared the likelihood of childhood abuse among sexual minorities vs sexual nonminorities. Results Sexual minority individuals were on average 3.8, 1.2, 1.7, and 2.4 times more likely to experience sexual abuse, parental physical abuse, or assault at school or to miss scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

36
423
3
25

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 617 publications
(499 citation statements)
references
References 71 publications
36
423
3
25
Order By: Relevance
“…First, sexual-minority adolescents reported higher prevalence rates than heterosexual youth for sexual abuse offline, problematic sexual meetings offline with person/s met online and online harassment. The findings concerning sexual abuse are in line with previous findings [12] while there are to our knowledge no previous studies about adolescents' sexual orientation in relation to problematic sexual meetings offline with person/s met online. In general, sexual-minority youth in our study reported having met someone offline they first had met online more often than heterosexual youth, which is in line with previous findings [36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First, sexual-minority adolescents reported higher prevalence rates than heterosexual youth for sexual abuse offline, problematic sexual meetings offline with person/s met online and online harassment. The findings concerning sexual abuse are in line with previous findings [12] while there are to our knowledge no previous studies about adolescents' sexual orientation in relation to problematic sexual meetings offline with person/s met online. In general, sexual-minority youth in our study reported having met someone offline they first had met online more often than heterosexual youth, which is in line with previous findings [36].…”
Section: Discussionsupporting
confidence: 91%
“…The similarity of the results for both measures of sexual orientation suggests that the findings are robust. This is in line with a meta-analysis of disparities in childhood sexual abuse, parental physical abuse, and peer victimisation among sexual-minority and sexual-non-minority youth which found that the dimension used to assess sexual orientation did not moderate the association between sexual orientation and victimisation [12].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…7 One population that may be at an increased risk of misusing AAS is sexual minority (gay and bisexual) boys. Sexual minorities are at an increased risk for a variety of maladaptive outcomes, including substance use, [8][9][10] depression, 11 victimization, [12][13][14] suicidality, 9,11,15 and body image dissatisfaction. 16 There are likely a number of reasons to explain these health disparities, with one prominent theory being the sexual minority stress model.…”
mentioning
confidence: 99%
“…In a meta-analysis of North American students, childhood sexual abuse was reported by 40 % of bisexual, 32 % of lesbian and 17 % of heterosexual women. 33 Compared to heterosexual women, bisexual women report higher rates of physical assault, injury by a partner, sexual assault, and lifetime victimization. 34 While the SAVA paradigm recognizes that women dealing with substance use and HIV also often experience violence, sexual minority status within this population may amplify this risk, with high-risk sex and substance use as mediators.…”
Section: Introductionmentioning
confidence: 99%